(untitled) (World Marxist Review, 2026)
In May 2025, the University of Chicago Press issued the 600-page volume, Karl Marx in America. The author is Andrew Hartman, a Professor of History at Illinois State University. The work, from a distinctive perspective, traces the deep impact of Marx's thought across disparate stages of American history, revealing the complex mechanisms through which his thought entered and shaped American political, economic and social discourse. Hartman seeks to dismantle the long-standing myth of America as a nation "naturally immune to Marxism", employing solid historical analysis to substantiate the claim that Marx's critical apparatus and theoretical insights offer an essential framework for comprehending the contradictions, conflicts and transformations of American capitalist society. Given that a Chinese translation of this work is not yet available, this article will initially provide a detailed introduction to its core arguments and the specific content of each chapter. Thereafter, the study will be contextualized in the expansive backdrop of intellectual history since the 20th century and the evolution of American society to investigate its academic value and practical significance, concluding with an evaluation of its identified limitations.